The Impact of Multichannel Marketing Strategy Implementation, HR Skills, and Customer Experience on Increased Sales in Small and Medium Enterprises - Supriadi, Adih; Kusumaningsih, Ani; Rukmana, Arief Yanto; Prayetno, Bambang Eko (Westscience Press, 2024)
This study investigates the impact of multichannel marketing strategy implementation, human resource (HR) skills, and customer experience on increasing sales in small and medium enterprises (SMEs). Employing a quantitative research approach, data were collected from 190 SME representatives using a 5-point Likert scale and analyzed with Structural Equation Modeling-Partial Least Squares (SEM-PLS 3). The findings reveal that all three factors—multichannel marketing strategy, HR skills, and customer experience—have a positive and significant effect on sales performance. Among them, HR skills exhibit the strongest influence, followed by multichannel marketing strategy and customer experience. These results underscore the importance of integrating effective marketing strategies, enhancing HR competencies, and delivering superior customer experiences to drive sales growth in SMEs. The study provides valuable insights for SME practitioners and policymakers, emphasizing the need for a holistic approach to improving business performance through strategic investments in marketing, HR, and customer experience.